2023
DOI: 10.1021/acs.inorgchem.2c04366
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Organic Framework/g-C3N4 van der Waals Heterojunction toward H2 Production

Abstract: Photocatalytic water splitting into H 2 is the most economic and environmentally friendly strategy for H 2 production, and rationally constructing a heterojunction retains enormous influence on a photocatalytic system. Herein, 2D/2D covalent organic framework/graphitic carbon nitride (COF/CN) van der Waals heterojunctions were readily prepared via an ultrasonic method for high-efficiency visible-light photocatalytic H 2 production. The photocatalytic H 2 production performance of optimized COF/CN composites ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In the UNCS( X ) heterostructures, the UN and CS semiconductors can interact via van der Waal interactions due to the presence of polar functional groups. 42 In addition, at the interface, the Cu + ions can coordinate with the –NH 2 group of the 2-amino terephthalic acid ligand in the UN structure. These interactions are responsible for the apparent changes in the Raman spectra of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…In the UNCS( X ) heterostructures, the UN and CS semiconductors can interact via van der Waal interactions due to the presence of polar functional groups. 42 In addition, at the interface, the Cu + ions can coordinate with the –NH 2 group of the 2-amino terephthalic acid ligand in the UN structure. These interactions are responsible for the apparent changes in the Raman spectra of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Mott–Schottky (M-S) plots for ZnIn 2 S 4 and Ni–Al LDHs were used to determine the flat band potential ( E fb ) at different frequencies, as illustrated in Figure c,d. The linear sections of M–S plots display positive slopes, revealing that ZnIn 2 S 4 and Ni–Al LDHs present n-type semiconductor properties . The E fb values of ZnIn 2 S 4 and Ni–Al LDHs were measured to be −0.96 and −0.82 V ( vs Ag/AgCl) by calculating the intercepts of the extrapolated linear section, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The linear sections of M−S plots display positive slopes, revealing that ZnIn 2 S 4 and Ni−Al LDHs present n-type semiconductor properties. 59 The E fb values of ZnIn 2 S 4 and Ni−Al LDHs were measured to be −0.96 and −0.82 V (vs Ag/ AgCl) by calculating the intercepts of the extrapolated linear section, respectively. According to eq 2, the E fb is converted to be −0.76 and −0.62 V (vs NHE) for ZnIn 2 S 4 and Ni−Al LDHs, respectively.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…Wang et al reported a COF/g-C 3 N 4 van der Waals heterojunction via an ultrasonic strategy. 141 With an increase in COF content, the COF/g-C 3 N 4 heterojunction showed a significant red-shifting of the absorption band according to UV-vis diffuse reflectance spectroscopy, which demonstrated the enhanced photoresponse of the composite. The steady-state photoluminescence (PL) spectroscopy intensity of the COF/g-C 3 N 4 heterojunction was lower than that of bare g-C 3 N 4 , further evidencing that the COF/g-C 3 N 4 heterojunction exhibits a reduced electron–hole complexation rate.…”
Section: Different Design Strategies For Cof-based Photocatalytic Hyd...mentioning
confidence: 93%